Microbial (E)-4-hydroxy-3-methylbut-2-enyl pyrophosphate reductase (IspH) and its biotechnological potential: A mini review - Huang, Shiyong; Xue, Yanfen; Ma, Yanhe; Zhou, Cheng (Frontiers in Bioengineering and Biotechnology, 2022)
(E)-4-hydroxy-3-methylbut-2-enyl pyrophosphate (HMBPP) reductase (IspH) is a [4Fe-4S] cluster-containing enzyme, which involved in isoprenoid biosynthesis as the final enzyme of methylerythritol phosphate (MEP) pathway found in many bacteria as well as in malaria parasites. In recent years, many studies have also revealed that isoprenoid compounds are an alternative to petroleum-derived fuels. Thus, ecofriendly methods harnessing the MEP pathway of microbes to synthesize isoprenoid compounds and IspH itself, have received notable attention from researchers. In addition to its applications in the field of biosynthesis, IspH is thought to be an attractive drug target for infectious diseases such as malaria and tuberculosis due to its indispensability for survival in most pathogenic bacterium and absent in human. In this mini-review, we summarize the previous reports for systematically illuminating the fundamental and structural properties, substrate binding and catalysis, proposed catalytic mechanism as well as some novel catalytic activities of IspH. Potential bioengineering and biotechnological applications of IspH are also discussed.